Congenital sudoriferous cyst of the orbit: A case report and review of literature - Parit S Ladani; Hermann Sailer; Sandeep M Thadani; Mita Shah (Wolters Kluwer Medknow Publications, 2017)
Apocrine gland cyst (sudoriferous cyst and apocrine hidrocystoma) is fairly uncommon in the eyelid, where it derives from the apocrine glands of Moll. In rare instances, an apocrine gland cyst can occur in the anterior portion of the orbit. If an orbital cyst affects the globe or extraocular muscles, it should be excised as soon as possible to prevent strabismus and amblyopia. Herewith, we are presenting the case of sudoriferous cyst in a 9-year-old child managed with surgical excision.